Ecological Aspects of Urban Structure of The Pangururan District - Alifa Azzahra Nasution (Talenta Publisher, 2021)
Urban structure is a city-forming arrangement that has many meanings depending on the indicators used. Ecological approach as one of the indicators is defined as a study of the spatial and temporal relationships of humans which are influenced by forces, selective, distributive, and accommodative of the environment. Pangururan district located in Samosir Regency, North Sumatra Province, Indonesia is one of the areas that is becoming the main focus of tourism development in Indonesia. This has led to the development of the city. The research was conducted using qualitative methods with data collection methods through literature studies and aerial observations. This study aims to determine how the structure of the Pangururan District is analyzed using the ecological theory of urban structure.